Ending uncertainty: Recapitalisation under European Central Bank supervision - Silvia Merler; Guntram B. Wolff (Bruegel, 2013)
Estimates of the recapitalisation needs of the euro-area banking system vary between exteuro50 and exteuro600 billion. The range shows the considerable uncertainty about the quality of banks' balance sheets and about the parameters of the forthcoming European Central Bank stress tests, including the treatment of sovereign debt and systemic risk. Uncertainty also prevails about the rules and discretion that will applyto bank recapitalisation, bank restructuring and bank resolution in 2014 and beyond. The ECB should communicate the relevant parameters of its exercise early and in detail to give time to the private sector to find solutions. The ECB should establish itself as a tough supervisor and force non-viable banks into restructuring. This could lead to short-term financial volatility, but it should be weighed against the cost of a durably weak banking system and the credibility risk to the ECB. The ECB may need to provide large amounts of liquidity to the financial system. Governments should support the ECB, accept cross-border bank mergers and substantial creditor involvement under clear bail-in rules and should be prepared to recapitalise banks. Governments should agree on the eventual creation of a single resolution mechanism with efficient and fast decision-making procedures, and which can exercise discretion where necessary. A resolution fund, even when fully built-up, needs to have a common fiscal backstop to be credible.
Keywords: 330; Bankenliquidität; Bankenaufsicht; Kapitalbedarf; Eurozone